Synthesis, photophysical characterization and biological evaluation of promising theranostic agents for cancer - Aguiar, Marcia Alexandra de Campos (2018)
Dissertação de Mestrado em Química Medicinal apresentada à Faculdade de Ciências e Tecnologia